Features of humoral answer in experimental animal tularemia with different sensitivity to infection - A. A. Gorbatov (Sankt-Peterburg : NIIÈM imeni Pastera, 2019)
Tularemia is an anthropozoonotic infection caused by Francisella tularensis. In clinical and sanitary-epidemiological practice, traditional diagnostics methods in tularemia are based on serological assays for detecting specific antibodies, allowing to diagnose it and estimate durability of patients’ immunity after vaccination. Previously, it was shown that specific serum antibodies in patients recovered after tularemia, unlike to those vaccinated with the live tularemia vaccine F. tularensis 15 NIIEG, can interact with specific epitopes on lipopolysaccharides isolated from strains of various subspecies — F. tularensis (Ft) and F. novicida (LPS Fn), while LPS Fn-specific immunoglobulins are lacked in the blood of vaccinated individuals. A set of experiments on identifying antibodies with similar specificity in laboratory animals of various species — mice, guinea pigs and rats with differed sensitivity to tularemia, administered with live tularemia vaccine strain as well as virulent F. tularensis strains to simulate vaccine-mediated and infectious processes, respectively was conducted. A methodical approach has been developed that allows to analyze humoral response in modelled infectious process in animals highly sensitive to tularemia such as BALB/c mice and guinea pigs that consisted of preliminary immunization with live tularemia vaccine followed by infection with virulent F. tularensis strains. It was shown that induction of specific anti-LPS Ft antibodies occured in these animal species, both after vaccination and infection with virulent strains. It was noted that, unlike guinea pigs and rats, mice both during vaccination and infection were characterized by significantly lower titers of LPS Ft-specific antibodies. However, no specific interaction between mouse serum and LPS Fn might be detected. Moreover, two types of immunoglobulins with different antigen specificities to the LPS Ft and LPS Fn epitopes were detected by dot-blot analysis in guinea pigs immunized with live tularemia vaccine, followed by infection with a virulent strain. In addition, antibodies to LPS Fn were also detected in the serum of rats infected with virulent, but not vaccine-based, F. tularensis strains. Thus, previous experimental data on the production of immunoglobulins with different antigenic specificity were confirmed in an experimental tularemia modelled in rats and guinea pigs that demonstrated a diagnostic significance and feasibility of using LPS Fn to confirm tularemia infection in humans.